Drug-Repositioning Approaches Based on Medical and Life Science Databases - Zamami, Yoshito; Hamano, Hirofumi; Niimura, Takahiro; Aizawa, Fuka; Yagi, Kenta; Goda, Mitsuhiro; Izawa-Ishizawa, Yuki; Ishizawa, Keisuke (Frontiers in Pharmacology, 2021)
Drug repositioning is a drug discovery strategy in which an existing drug is utilized as a therapeutic agent for a different disease. As information regarding the safety, pharmacokinetics, and formulation of existing drugs is already available, the cost and time required for drug development is reduced. Conventional drug repositioning has been dominated by a method involving the search for candidate drugs that act on the target molecules of an organism in a diseased state through basic research. However, recently, information hosted on medical information and life science databases have been used in translational research to bridge the gap between basic research in drug repositioning and clinical application. Here, we review an example of drug repositioning wherein candidate drugs were found and their mechanisms of action against a novel therapeutic target were identified via a basic research method that combines the findings retrieved from various medical and life science databases.